STUDI KOMPARASI ALAT BANTU PENGELOLA KEUANGAN PRIBADI BERBASIS MOBILE: COMPARATIVE STUDY MOBILE BASED PERSONAL FINANCIAL MANAGEMENT ASSISTANCE - Liana Dewi; Rohmat Gunawan (Program Studi Teknologi Informasi, 2019)
Managing personal finance is simpler than managing a company's finances. The increasing cost of living is one of the reasons for the importance of managing personal finance so that it is not trapped in poor financial conditions. Managing finance begins with understanding the concepts of income and expenditure. A variety of mobile applications are available that can be used to facilitate financial records and planning, so you need to choose and understand the features of the application before using it. This study aims to conduct a comparative study of mobile-based personal finance management tools. Recording of financial transactions is attempted using three different financial management applications, including: My money, Wallet and Monefy. Receipt budget data, expenditure budget data and their realization are prepared in this study to be inputted and processed using the three applications. After the experiment, a comparison was made using eight parameters. Experimental results in the study show that my Money, Wallet and Monefy applications each have standard features that can be used as a tool in conducting standard financial management. But for more facilities, Wallet provides additional various types of financial statements, while Monefy provides features of currency exchange and synchronization